Properties of Oil Palm (Elaeis Guineensis Jacq.) Empty Fruit Bunch Fibres-Polypropylene Composites - Manarpaac, Gloria A. (2001)
The technical viability of using oil palm empty fruit bunch (EFB) fibres as fillers and/or reinforcements to polypropylene was investigated. The effects of moisture content (MC), fibre size, fibre loading, concentration of maleated polypropylene (MAPP), modes of electron beam (EB) irradiation, types and concentration of reactive additives (RAs) on the physical, chemical, morphological, mechanical, dimensional stability and thermal properties of EFB-PP composites were investigated. EFB-PP composites were prepared from thermomechanically pulped EFB fibres and PP by melt-mixing them using a Brabender Plastic Corder PL-2000- 6 at 180°C and compressing them in a hot-and-cold press machine. Properties of the composites were tested using ASTM standards. Results were subjected to Analysis of Variance (ANOVA) and Student-Newman-Keuls (S-N-K) multiple comparison of means. The influence of the initial MC and sizes of EFB fibres on the properties of the EFB-PP composites were not so Significant, although, the mixing torque of blends were affected where higher Me and longer fibres gave higher mixing torque. The effects of different fibre loadings and concentrations of MAPP, however, were noteworthy. The mixing torque increased with increasing fibre loading up to 50% fibres then decreasing at higher loadings. The melt flow rate (MFR) Of the composites reduced extensively with the addition of fibres and no flow was observed above 50% fibres. The density and Me of the composite boards also increased with increasing fibre content. The tensile and flexural strengths of the composites decreased with increasing fibre loading along with elongation at break and hardness while tensile and flexural modulus increased significantly. Their impact strengths increased for notched specimens while it decreased for the unnotched specimens. Water absorption and thickness swelling increased tremendously with the addition of more EFB fibres in the composites. Addition of MAPP caused a reduction in the mixing torque of the composite blends and an increase in the MFR of the composite melts. Two-percent MAPP, the optimum level of coupling agent addition, caused an increase in the density and Me of the boards, reduced fibre breakage during compounding, and improved most of the properties.